Pungency of hybrid chilli making life sweeter - Reddy, K Madhavi; Sadashiva, A T; Singh, T H (Indian Horticulture, 2019)
Initially due to small flower size and low seed content per act of pollination, F 1 hybrid seed production was not economical in chilli. With the development and commercial exploitation of male sterile systems in chilli, the scope for economized F 1 hybrid seed production increased and thus its cultivation. Due to increased availability and also cultivation of high-yielding F 1 hybrids in country, productivity of dry chilli increased from 0.9 to 1.8 tonnes/ha (doubled).